Validity of the Kansas squat test for track and field sprinters and jumpers - Luebbers, P.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2010)
The ability to generate power is an essential component to achieving optimal performance in several track and field events, particularly the throws, sprints and jumps. The Wingate Anaerobic Test (WAnT) is one of the most established forms of standardized anaerobic power testing. The WAnTis performed utilizing a cycle ergometer and has been shown to be both reliable and valid. Sprinters and jumpers train for power using a combination of running and strength training techniques. The WAnT may be appropriate for testing the running component of training due to its cyclical nature, but it might not be the most fitting test for addressing the more linear weight lifting component. A lift-specific power test could allow for a more comprehensive assessment of the trained status of sprinters and jumpers than a cyclic test alone. The Kansas Squat Test (KST) is a repetitive lifting test that has been designed to measure similar indices of power as the WAnT. To examine the relationship between the WAnT and the KST on measures of Peak Power (PP), Average Power (AP), Minimum Power (MP), Fatigue [% Power Drop (FTG)], and Post-test Lactate (La) for collegiate track and field sprinters and jumpers. Seven male (72.91 +/- 10.0kg, 180.70 +/- 4.0cm) and seven female (64.43 +/- 5.05kg, 171.63 +/- 3.55cm) members of a collegiate track and field sprinters and jumpers squad participated in this study. Each participant completed separate familiarization sessions with both the WAnT and KST prior to the data collection sessions. A 1-RM squat was determined using a smith machine, also during an individual session. The data collection sessions were conducted at the beginning of track practice, separated by one week. The WAnT 30-second test was performed using a cycle ergometer with resistance set at 0.07 kg[middle dot]BM. The KST was performed using the smith machine and consisted of 15 repetitions of speed squat at a cadence of 1 lift[middle dot]6 sec-1. The external KST load was calculated using the system mass as ((BM + 1 -RM)[middle dot]0.70)-BM. KST power measures were determined using an external dynamometer utilizing system mass (BM + KST Load). Pre- and post-test lactate concentrations were also recorded. Pearson correlations between the WAnT and KST are as follows: PP, r = .869**; AP, r = .875**; MP, r = .839*; FGT, r = -.369; La, r = .110 (**p<0.01; *p<0.05). These data indicate that the KST is a feasible alternative to the WAnT for measuring Peak, Average and Minimum Power for sprinters and jumpers. Collegiate track and field sprinters and jumpers train for power using both running and weightlifting exercises. The current study demonstrates a potential testing method that is lift-specific which, when incorporated into a testing battery, may aid in providing a more comprehensive analysis of the athletes'power status.